Comparative Effectiveness of Date Palm Extract and Almond Milk on Breast Milk Production among Lactating Mothers: A Multicenter Quasi-Experimental Study - Imroatul Azizah; Riza Faulina; Tantri; Nuryanti Komalasari; Ana Noviyanti; Oktavia Sandha; Endah Widiawati (Journal of Innovative and Creativity, 2026)
Exclusive breastfeeding is essential for infant growth and development; however, many mothers experience difficulties in maintaining adequate milk production during the early postpartum period. Natural galactagogues such as date palm extract (Phoenix dactylifera) and almond milk (Prunus dulcis) are traditionally believed to enhance breast milk volume, but evidence from comparative multicenter studies remains limited. This study aimed to compare the effectiveness of date palm extract and almond milk on breast milk production among lactating mothers. A multicenter quasi-experimental pre–post design was conducted in five health centers in Indonesia between 2025. A total of 100 postpartum mothers who met inclusion criteria were divided equally into two intervention groups: date palm extract (n = 50) and almond milk (n = 50). Participants consumed the assigned intervention twice daily for 14 consecutive days. Breast milk volume was measured using the test-weighing method before and after the intervention. Data were analyzed using paired and independent t-tests with a significance level of 0.05. Both interventions significantly increased breast milk volume (p < 0.05). The mean increase was greater in the date palm extract group (mean ± SD: 6.25 ± 4.10 ml) than in the almond milk group (3.90 ± 4.60 ml), with a mean difference of 2.35 ml (95% CI: 0.42–4.28; p = 0.018). No adverse effects were reported among participants. Date palm extract and almond milk were both effective in enhancing breast milk production, but date palm extract showed a more consistent and higher effect across study sites. Further randomized controlled trials with larger sample sizes are recommended to confirm these findings and to explore biochemical mechanisms underlying the lactogenic effects